Water treatment : plant performance evaluations and operations. - O'Connor, John, ....-; O'Connor, Tom, ....-; Twait, Rick, ....- (Hoboken : Wiley, 2009)
Water treatment is a growing field in North America, with seventy US states and localities and ten Canadian provinces requiring certification for water treatment plant operators. This book provides a step-by-step look at the most current water treatment technologies, balancing academic theory and professional practice. A compilation of studies conducted over the past decade at the Bloomington, Illinois Water Treatment Plant, it presents studies that are useful as templates for comparable long-term studies at other water utilities. This is an unparalleled gathering of techniques, processes, and data, including test results for every potential taste and odor control method.